Geometria e ensino híbrido... você já ouviu falar? uma formação continuada de professores do Ensino Fundamental I - Rodrigues, Renata Udvary (2019)
This work is part of the research group TECMEM - Technologies and Means of Expression in Mathematics, and refers to a continuous formation in Geometry, based on aspects of the Flipped Classroom model, through the Moodle environment, and with support of GeoGebra software, offered to Elementary School I teachers. These professionals consider that teaching the first mathematical notions in the early years is a special and challenging task, since the subjects related to the knowledge of Mathematics in initial education do not prepare them sufficiently for teaching the contents determined by the pedagogical plan. Research points to the fragile preparation of Mathematics contents regarding their theoretical deepening for teaching in the early years, causing a detrimental development of students. Thus, this research aimed to verify if a continuing education based on the model mentioned above can create conditions for the development of teacher autonomy about the updating of their knowledge, as well as the improvement of their teaching practice. As a complementary question, the present work seeks to investigate what the perception of these teachers regarding the use of technological resource is, including GeoGebra software to improve the knowledge in Geometry. To this end, was prepared the project: “Geometry and Blended Learning ... Have you heard?”, which was developed with teacher educators, from elementary schools I (1st to 5th grade) of São Paulo municipal public network, organized and selected by the coordinating teacher of the Board of Education. For the development of the work, modules with basic geometric contents were provided with moments of theoretical reflections; practical activities and face-to-face meetings with the participating teachers, ensuring active participation. The research was qualitative, with theoretical basis of Technological, Pedagogical and Content Knowledge, TPCK, and methodology of Design Research or Design Experiments, aiming at the improvement of the project for future teacher training. For data collection, we used questionnaires, teachers’ protocols, researcher observations during face-to-face meetings, feedbacks obtained from the Moodle platform forums in proposed activities. The final questionnaire analysis was divided into four categories: “Understanding the Flipped Classroom Model”; “Adequacy of the geometry contents worked in the formation”; “About the use of GeoGebra software as a digital tool to help teach geometry” and “Reflections on the whole process, with suggestions for improving this formation”. Even with the emergence of some dependent and independent variables pointed out in Design Research, which limited some aspects at the beginning of the training requiring some changes and adjustments in its continuity, it can be stated that the model adopted in this research is promising in favor of, facilitate and promote the improvement of teachers' knowledge for better professional practice. Participants pointed to the advantages and benefits of using the Flipped Classroom as a model, not only for continuing education, but also for initial training. Regarding the importance of teaching geometry with the use of digital technologies, in this case the GeoGebra software, its use made it possible to understand some concepts developed in the training, which the teachers did not have, totally or partially, or, although they had, they couldn't understand them until then